PENERAPAN MODEL PEMBELAJARAN KOOPERATF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 5 TANJUNG PUNAK - Zubaidah Zubaidah; Lazim N Lazim N; Zairul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This Research of background by lowering of result learn IPS class of III SDN 5 Foreland of Punak at subject of IPS. Visible of Complete Criterion of Minimun the specified by school that is 70, from 20 class student people of III tired [of] KKM is 10 student people (50.00%) and which do not reach KKM is 50 student people ( 50.00%) with class mean 65,85. Intention of this research is to improve result learn IPS class student of III SDN 5 Foreland of Punak with applying of model study of type co-operative of Picture picture and. This research present result learn which is obtained from Daily Restating value before action with mean 65.85 mounting to become 77,48 at cycle of I, and mount again become 80,95 at cycle of II. Activity learn at cycle of I first meeting is 58% with criterion enough, both/ second meeting with value 71% with good criterion. At cycle of II first meeting, activity learn is 79% with good criterion, and at both/ second meeting is 87% with criterion very goodness. Student activity at cycle of I first meeting is 63% with good criterion, both/ second meeting is 67% with good criterion. At cycle of II first meeting, student activity is 79% with good category, and at both/ second meeting is 83% with criterion very goodness. Pursuant to result of research, can be proved that applying of model study of type co-operative of Picture picture and can improve result learn IPS class student of III SDN 5 Foreland of PunakKeyword: Picture and picture, result learn IPS